(untitled) (Physical Education, Health and Social Sciences, 2026)
Freshwater ecosystems, despite comprising less than 1% of Earth’s surface, harbor disproportionate biodiversity, supporting 10% of known species and facing unprecedented decline rates exceeding those in terrestrial or marine environments. This review synthesizes the global status of freshwater biodiversity loss, highlighting taxonomic vulnerabilities among fishes (26-33% threatened), decapod crustaceans (30%), odonates (16%), and molluscs ( 36%), driven by habitat fragmentation, pollution, invasive species, and hydrological alterations. Quantitative analyses reveal extinction rates 100 times above background levels, with regional hotspots in North America and Europe. The paper examines genetic implications of fragmentation, functional shifts from chemical pollution, and advanced indicators like the Index of Biotic Integrity (IBI), environmental DNA (eDNA), and remote sensing for ecosystem health assessment. Conservation strategies emphasize Freshwater Protected Areas, Nature-Based Solutions (NBS), and policy frameworks such as the Kunming-Montreal Global Biodiversity Framework and Ramsar Convention. Case studies from Lake Victoria and the Mekong River illustrate synergistic threats and restoration potential. Urgent, integrated actions are essential to bend the curve of biodiversity loss and sustain ecosystem services amid intensifying anthropogenic pressures.